The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1365-2729.2004.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of Palm and wearable computers for Participatory Simulations

Abstract: Recent educational computer-based technologies have offered promising lines of research that promote social constructivist learning goals, develop skills required to operate in a knowledge-based economy (Roschelle et al. 2000), and enable more authentic science-like problem-solving. In our research programme, we have been interested in combining these aims for curricular reform in school science by developing innovative and progressive handheld and wearable computational learning tools. This paper reports on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 24 publications
(44 reference statements)
1
28
0
4
Order By: Relevance
“…Donde los estudiantes analizan sus acciones sin la participación del profesor; por ejemplo, en el aprendizaje colaborativo de conceptos de herencia genética mendeliana, a través de la participación simulada mediada por soportes computacionales portátiles (Klopfer, Yoon & Rivas, 2004).  Procesos mediados por el profesor.…”
Section: Fase De Desarrollounclassified
See 1 more Smart Citation
“…Donde los estudiantes analizan sus acciones sin la participación del profesor; por ejemplo, en el aprendizaje colaborativo de conceptos de herencia genética mendeliana, a través de la participación simulada mediada por soportes computacionales portátiles (Klopfer, Yoon & Rivas, 2004).  Procesos mediados por el profesor.…”
Section: Fase De Desarrollounclassified
“… Schematic representation (Van Amelsvoort, Andriessen & Kanselaar, 2007).  Proyectos de participación (Robertson & Howells, 2008) Reflexión  Procesos autónomos (Klopfer, Yoon & Rivas, 2004)  Procesos mediados (Nussbaum, Alvarez, McFarlane, Gomez, Claro, & Radovic, 2009). …”
Section: Construcción Y Ejecución De Estrategiaunclassified
“…• Klopfer et al [12] showed that the newer and more easily distributable version of Participatory Simulations on handhelds was equally as capable as the original Tag-based simulations in engaging students collaboratively in a complex problem-solving task. They feel that handhelds technology holds great promise for promoting collaborative learning as teachers struggle to find authentic ways to integrate technology into the classroom in addition to engaging and motivating students to learn science.…”
Section: Related Workmentioning
confidence: 99%
“…Some research groups have implemented collaborative learning participatory simulations with handhelds and infrared beaming [16], and it has been found that this kind of activities provide various advantages for teaching and learning: (a) they introduce an effective instructional tool and have the potential to impact student learning positively across curricular topics and instructional activities [18], (b) they increase the motivation [12], [4], and (c) they generate positive effects in engagement, self-directed learning and problemsolving [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some research groups have implemented participatory simulations with handhelds and infrared beaming [15], and it has been found that this kind of activities provide various advantages for teaching and learning: (a) they introduce an effective instructional tool and have the potential to impact student learning positively across curricular topics and instructional activities [16], (b) they increase the motivation [11], [5], and (c) they generate positive effects in engagement, self-directed learning and problem-solving [11].…”
Section: Introductionmentioning
confidence: 99%